सानताड़ी पारसी उनुरूम (संताली भाषा परिचय) - Krishna Chandra Tudu (Santali Sahitya Parishad, Rajdoha, East Singhbhum, Jharkhand, 2016)
The book provides in detailed about Santali Language, its scripts and grammar.
An Introduction to the Santali Language
Keywords: Grammar; Santali